Beyond the risk factors of sports-related match-fixing: testing the applicability of situational action theory - Vanwersch, Lucie (European journal of criminology, 2024)
Despite the increasing academic interest in match-fixing, little is known about the behavioral determinants of this phenomenon. This study applies key theoretical concepts of situational action theory (SAT) to sportspersons’ decision-making process when confronted with sports-related match-fixing (SRMF) propositions. Using a factorial survey, amateur football players (n = 661), and tennis players (n = 609) in Flanders (Belgium) were asked to evaluate hypothetical realistic situations containing match-fixing propositions. Our results show that sportspersons’ crime propensity, mostly determined by their moral judgment of SRMF and self-control, and their levels of temptation, together with a number of SAT interactions, were the best predictors of SRMF as a form of sports-related rule breaking. We conclude that SAT provides a valuable theoretical framework to study fraud in sports phenomena such as SRMF, and that factorial surveys have great potential to allow researchers to reach beyond the risk factor stage of research, to efficiently inform prevention initiatives.